Feasible techniques in robotic thoracoscopic repair of congenital esophageal atresia: case report and literature review - Shuai Li; Guoqing Cao; Rongchao Zhou; Xi Zhang; Ying Zhou; Shao-tao Tang (Surgical Case Reports)
Abstract Background Robotic repair for esophageal atresia (EA) using da Vinci system is challenging. Specific surgical techniques need to be explored to overcome the current hurdles. Case presentation Two cases with EA (type I and type III by Gross classification, respectively) were repaired using da Vinci robotic system. Step trocar insertion and asymmetric ports distribution techniques were used. The mean weight was 3.2 kg. Operative times were 95 min totally, with the anastomotic time of 27.5 min. Follow-up duration was 12 months. Esophageal fistula reoccurred in one case. None was confirmed anastomotic stricture. Conclusion Step trocar insertion procedure and asymmetric ports distribution technique are effective in robotic esophageal atresia.